An implementation model for managing cloud-based longitudinal care plans for children with medical complexity. (5th November 2020) - Wang, Grace; Wignall, Julia; Kinard, Dylan; Singh, Vidhi; Foster, Carolyn; Adams, Sherri; Pratt, Wanda; Desai, Arti D
Abstract: Objective: We aimed to iteratively refine an implementation model for managing cloud-based longitudinal care plans (LCPs) for children with medical complexity (CMC). Materials and Methods: We conducted iterative 1-on-1 design sessions with CMC caregivers (ie, parents/legal guardians) and providers between August 2017 and March 2019. During audio-recorded sessions, we asked participants to walk through role-specific scenarios of how they would create, review, and edit an LCP using a cloud-based prototype, which we concurrently developed. Between sessions, we reviewed audio recordings to identify strategies that would mitigate barriers that participants reported relating to 4 processes for managing LCPs: (1) taking ownership, (2) sharing, (3) reviewing, and (4) editing. Analysis informed iterative implementation model revisions. Results: We conducted 30 design sessions, with 10 caregivers and 20 providers. Participants emphasized that cloud-based LCPs required a team of owners: the caregiver(s), a caregiver-designated clinician, and a care coordinator. Permission settings would need to include universal accessibility for emergency providers, team-level permission options, and some editing restrictions for caregivers. Notifications to review and edit the LCP should be sent to team members before and after clinic visits and after hospital encounters. Mitigating double documentation barriers would require alignment of data fields between the LCP and electronic health record to maximize interoperability. Discussion: These findings provide a model for how we may leverage emerging Health Insurance Portability and Accountability Act–compliant cloud computing technologies to support families and providers in comanaging health information for CMC. Conclusions: Utilizing these management strategies when implementing cloud-based LCPs has the potential to improve team-based care across settings.